2021
DOI: 10.5194/tc-15-1517-2021
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a grounding line fan at the onset of a basal channel under the ice shelf of Support Force Glacier, Antarctica, revealed by reflection seismics

Abstract: Abstract. Curvilinear channels on the surface of an ice shelf indicate the presence of large channels at the base. Modelling studies have shown that where these surface expressions intersect the grounding line, they coincide with the likely outflow of subglacial water. An understanding of the initiation and the ice–ocean evolution of the basal channels is required to understand the present behaviour and future dynamics of ice sheets and ice shelves. Here, we present focused active seismic and radar surveys of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Smith et al (2009) found an active subglacial lake at the transition between Academy Glacier and SFG, and also Humbert et al (2018) suggest in the upstream area of SFG a subglacial lake. Hofstede et al (2021a) showed that the subglacial channel appears 7 km upstream of the grounding line increasing its height to 280 m at the grounding line. The location of the channel corresponds with increased subglacial flux found by Humbert et al…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Smith et al (2009) found an active subglacial lake at the transition between Academy Glacier and SFG, and also Humbert et al (2018) suggest in the upstream area of SFG a subglacial lake. Hofstede et al (2021a) showed that the subglacial channel appears 7 km upstream of the grounding line increasing its height to 280 m at the grounding line. The location of the channel corresponds with increased subglacial flux found by Humbert et al…”
Section: Discussionmentioning
confidence: 99%
“…(2018) using a simple routing scheme. The channel formed on the grounded part is most likely the source of a grounding line fan and thus carrying sediments, formed at the seabed under the basal channel Hofstede et al (2021a). Once this topographic feature reaches the ocean, it will focus on the relatively buoyant flow and enhance shear-driven vertical mixing, bringing heat and salt to the ice base leading to higher basal melt rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2016-17, ~26,000 line-km of aerogeophysical data were acquired over Filchner and Brunt ice shelves (West Antarctica), as well as over outlet glaciers of English Coast (western Palmer Land, Antarctic Peninsula). Early findings from the 2016-17 aerogeophysical survey revealed subglacial drainage channels beneath Support Force Glacier (Hofstede et al, 2021), provided evidence for a large ~80 x 30 x 6 km mafic intrusion likely resulting from mantle melting during Gondwana break-up (Jordan and Becker, 2018), and helped to delineate the subglacial bathymetry beneath Brunt Ice Shelf (Hodgson et al, 2019).…”
Section: -2020mentioning
confidence: 99%